La Documentación en Rne - Anguiano Baños, Mónica; Cuesta Barruz, María Jesús; Perales Domínguez, María Elena; Sánchez Ortego, Sonia (Cuadernos de Documentación Multimedia, 2018)
La Documentación en Rne